"Warning: This image has been digitally altered": The effect of disclaimer labels added to fashion magazine shoots on women's body dissatisfaction. (June 2017) - Tiggemann, Marika; Brown, Zoe; Zaccardo, Mia; Thomas, Nicole
Highlights: Disclaimer labels on fashion shoot images do not protect body satisfaction. Size of disclaimer label has no effect. Internalisation of the thin ideal moderates the effect of disclaimer label on body dissatisfaction. Abstract: The present experiment aimed to investigate the impact of the addition of disclaimer labels to fashion magazine shoots on women's body dissatisfaction. Participants were 320 female undergraduate students who viewed fashion shoots containing a thin and attractive model with no disclaimer label, or a small, large, or very large disclaimer label, or product images. Although thin-ideal fashion shoot images resulted in greater body dissatisfaction than product images, there was no significant effect of disclaimer label. Internalisation of the thin ideal was found to moderate the effect of disclaimer label, such that internalisation predicted increased body dissatisfaction in the no label and small label conditions, but not in the larger label conditions. Overall, the results showed no benefit for any size of disclaimer label in ameliorating the negative effect of viewing thin-ideal media images. It was concluded that more extensive research is required before the effective implementation of disclaimer labels.